Effect of Carbohydrate, Caffeine, and Carbohydrate + Caffeine Mouth Rinsing on Intermittent Running Performance in Collegiate Male Lacrosse Athletes. Issue 9 (September 2017) - Dolan, Patrick; Witherbee, Kyle E.; Peterson, Kimi M.; Kerksick, Chad M.
Abstract : Abstract: Dolan, P, Witherbee, KE, Peterson, KM, and Kerksick, CM. Effect of carbohydrate, caffeine, and carbohydrate + caffeine mouth rinsing on intermittent running performance in collegiate male lacrosse athletes. J Strength Cond Res 31(9): 2473–2479, 2017—Recently, an interest has developed in the potential to rinse the oral cavity with key nutrients to impact various types of exercise and presumably sporting performance. Although multiple studies examining carbohydrate mouth rinsing have been completed, conflicting evidence surrounding caffeine mouth rinsing persists, and no research has explored its ability to impact high-intensity, intermittent running performance. This study investigated the independent and synergistic ability of carbohydrate and caffeine mouth rinsing to improve intermittent running performance. The Yo-Yo Intermittent Recovery Test-Level 1 (Yo-Yo Level 1) was completed in 10 collegiate (National Collegiate Athletic Association [NCAA] Division II) male lacrosse players after a 10-second mouth rinse with a solution of either carbohydrate (CHO), caffeine (CAF), carbohydrate + caffeine (CHO + CAF), placebo (H2 O), or a no rinse control (CON). No significant improvements in Yo-Yo IRT-1 performance were found ( p > 0.05). Perceptual indications of effort (i.e., rating of their perceived exertion [RPE]) were significantly lower ( p ⩽ 0.05) in CHO and CHO + CAF when compared with CON after speed level 11. Interestingly, RPE levels were nonsignificantly lower in all but one level of the Yo-Yo Level 1 for CHO in comparison with other groups. Carbohydrate and caffeine mouth rinsing seems to exert no impact on running performance before maximal intermittent running in a group of male collegiate lacrosse players.